All Days 2013
DOI: 10.2523/iptc-16529-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Tight Oil Reservoir Hydraulic Fracturing Stimulation Using Two Wells Simultaneous Micro Seismic Monitoring Approach

Abstract: The tight sand oil reservoir found in the Ordos basin is known for its very low porosity and permeability. Almost every well has been stimulated using hydraulic fracturing techniques. The average production for a vertical well is approximately 4–5 tons per day. Among such a large number of fracture jobs, enhanced production after stimulation does not always meet expectations. Since2005, hydraulic fracturing monitoring services have been carried out widely in this field to improve fracture geometry understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They argued that by correlating the results of the two techniques in parallel could provide valuable information about the local heterogeneity within the reservoir and the effect on the fracture simulation programs. Xu et al [45] presented results of microseismic monitoring of hydraulic fracturing simulation in a tight sand reservoir. They stated that although the use of a single well has been widely adopted, much better results could be obtained with a dual-well set up regarding fracture delineation and location accuracy.…”
Section: Shale Gas -New Aspects and Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…They argued that by correlating the results of the two techniques in parallel could provide valuable information about the local heterogeneity within the reservoir and the effect on the fracture simulation programs. Xu et al [45] presented results of microseismic monitoring of hydraulic fracturing simulation in a tight sand reservoir. They stated that although the use of a single well has been widely adopted, much better results could be obtained with a dual-well set up regarding fracture delineation and location accuracy.…”
Section: Shale Gas -New Aspects and Technologiesmentioning
confidence: 99%
“…Xu et al [45] studied the hydraulic fracturing stimulation using microseismic monitoring of two wells simultaneously in low porosity and low permeability formation in Ordos basin with the aim of improving fracture geometry and optimization of good placement. Comparing with single-well microseismic monitoring, they concluded that the dual-well technique could explain features in far more precise details and accuracy and then subsequently can reduce uncertainty.…”
Section: Shale Gas -New Aspects and Technologiesmentioning
confidence: 99%
“…As the basic principle of the monitoring process is through acoustic emission and seismology (Wang, 2008;1 ), microseismic events do not necessarily occur where the fracturing fluid arrives or where the fracture expands (Liu, 2012;2 ). But, it can be attributed to the characteristics of induced microseismic signals, such as different energy, weak signal, wide frequency band, and serious interference by background noise and low signal-to-noise ratio (SNR) which affects the accuracy, reliability, and subsequent interpretation of microseismic research (Kurdi et al, 2015).In comparison, the main mechanism of hydraulic fracture is tensile failure, while that of microseismic events with high amplitude is usually associated with shear failure (Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, one monitoring method may not be able to fully analyze and represent the reservoir properties. Hence, for a better understanding and analysis, the combination of variety of monitoring methods (Liu et al, 2014;Hickey et al, 2019;Young et al, 2020) is preferred.…”
Section: Introductionmentioning
confidence: 99%